Adaptive Optimization Method for Piled Raft Foundations Based on Variable Pile Spacing - Chenyang Yuan; Yunfei Xie; Mang Ou (Applied Sciences, 2023)
Stricter control of the differential settlement is always required in important buildings more than in ordinary buildings. It becomes a necessity to find a simple and efficient optimum design method for pile foundations in terms of performance and economy. In this paper, an adaptive optimization method (AOM) is proposed to reduce the differential settlement of the pile group and piled raft, in which the piles are located in appropriate locations according to the settlement characteristic of the raft. Piled raft foundations with different types of load and different raft shapes are optimized using this method; soil inhomogeneity and nonlinear characteristic are considered during this process. The optimization results show that the reductions of the differential settlement are more than 80%. The overall foundation performances are improved as the maximum settlements of the foundations are reduced. The maximum bearing capacity of the pile group is no more than its ultimate bearing capacity after optimization design, and part of the excess bearing capacity can be translated into economic savings (AOM-ES). By keeping a good optimization effect of the differential settlement, the number of piles can be reduced by AOM-ES compared with the initial design. The AOM is robust and can be applied to the piled foundations of various raft shapes in layered soils under complex vertical loads with no significant impact on optimization efficiency.